Quality of Sleep Among Patients with Chronic Renal Failure - Priyadharshini V. (International Journal of Emergency and Trauma Nursing and Practices, 2023)
Renal failure is the partial or complete impairment of kidney function. Inability to eliminate metabolic waste products and water, along with functional disruptions in all bodily systems, result in the condition known as renal failure. Renal failure can be categorized as either acute or chronic. Chronic renal failure refers to the gradual and irreversible deterioration of the nephrons in both kidneys. It is characterized by either kidney damage or a glomerular filtration rate below 60 ml/min. The last stage of kidney failure is called as End Stage Renal Disease, which occurs when the glomerular filtration rate is <15 mlmin. Need for the study: Most of patients experience sleep disturbance who had chronic kidney disease. This makes them irritable and anxious, tired, drowsy during day. Nurses should adequately assess and document sleep pattern disturbance in hospitalized patients. There is need of nursing care to improve quality of sleep. Statement of the Problem: “A Descriptive study to assess the Quality of Sleep Among Patients with Chronic Renal Failure at selected hospitals Coimbatore.” Objectives: The objective of the study was to determine the sleep quality among the chronic renal failure patients, associate sleep quality with selected demographic variable and clinical variables. Design and Sampling: Descriptive research design research design was used for this study. To choose the samples, a non-probability purposive sampling technique was used. Instruments: Data collection was collected by using the demographic and clinical profile questionnaire; the patients were clearly explained about the Pittsburgh Sleep Quality Index questionnaires Data was collected and analyzed using descriptive and inferential statistics. Discussion: overall sleep quality of patients with chronic renal failure during the data collection period, 13 of patients had the score of 11 to 21 indicated sleep disorder, 27 of patients had the score of 5 to 10 shows poor sleep quality, 10 (24%) of patients had the PQSI Score of <5, which indicated presence of good quality of sleep. Conclusion: The study result showed that most of the chronic renal failure patients having poor quality of sleep.
Keywords: CRF; PSQI; Pittsburgh Sleep Quality Index; chronic renal failure; demographic variable; metabolic waste products; sleep